Islamic Dakwah Strategy in the Cambodian Camp Community: An Analysis of Challenges and Opportunities - Ismail Nasution; Sobyan Salam (Feedback International Journal of Communication, 2024)
The Muslim community from Champa in Cambodia was initially welcomed by the ruling Khmer king. The primary ethnic groups among the Champa refugees were the Chams and Malays, who later formed a distinct Muslim community in Cambodia. The process of Islamization in Cambodia differs from other countries, as it was influenced by the migration of the Champa people following the Vietnamese expansion. Although Cambodia was not a major trading hub, it was a significant rice producer before the collapse of the Champa Kingdom in the 15th century, and had long-standing trade and cultural ties with the Malays. This study aims to analyze the strategies of Islamic da'wah (propagation) among the Cham community in Cambodia and to evaluate the challenges and opportunities in spreading Islam in the region. A qualitative approach was employed, utilizing in-depth interviews, field observations, and document analysis. The findings reveal that the da'wah strategy in the Cham community focuses on cultural and social integration, with preachers adapting their messages to align with local customs and traditions. This approach has been effective in fostering positive relationships and improving religious understanding. However, challenges such as language barriers, limited resources, and resistance to change persist. The study emphasizes the need for innovative and context-sensitive da'wah strategies, as well as adequate training and support for preachers. In conclusion, the Islamic da'wah strategy in Cambodian Cham society requires continuous adaptation to overcome challenges and leverage opportunities.